Spatial distribution and abundance of the megabenthic fauna community in Gabes gulf (Tunisia, eastern Mediterranean Sea) - EL LAKHRACH, H.; HATTOUR, A.; JARBOUI, O.; ELHASNI, K.; RAMOS-ESPLA, A.A. (Mediterranean Marine Science, 2012)
The aim of this paper is to bring to light the knowledge of marine diversity of invertebrates in Gabes gulf. The spatial distribution of the megabenthic fauna community in Gabes gulf (Tunisia, Eastern Mediterranean Sea), together with the bottom type and vegetation cover, were studied. The abundance of the megabenthic fauna was represented by eight groups: Echinodermata (38%), Crustacea (21%), Tunicata (19%), Mollusca (13%), Porifera (4%), Cnidaria (3%), Bryozoa, and Annelida (2%). It was spatially more concentrated in the coast area of the gulf than in the offshore waters. This area, especially, in Southern Kerkennah, North-est of Gabes and North-east of Djerba appeared to be in a good ecological condition hosting a variety of species like the paguridsPaguristes eremita and Pagurus cuanensis, the brachyura Medorippe lanata, Inachus doresttensis, the Gastropoda Hexaplex trunculus, Bolinus brandaris, Aporrhais pespelecani, andErosaria turdus, the Bivalvia Fulvia fragilis, the Echinoidea Psammechinus microtuberculatus, Holothuria polii,Ophiothrix fragilis and Antedon mediterranea, and the AscidiaceaAplidium cf. conicum, Didemnum spp, and Microcosmus exasperatus. The species’ compositions of the megabentic fauna community showed clearly that the spatial analysis represented the differences between the community of these two regions (inshore waters and offshore waters). These differences were closely related to peculiar characters of the fauna and biotopes (depth, bottom type and vegetation cover community). The results of the present study should be considered as a necessary starting point for a further analysis of priceless benthic fauna contribution to the marine environment and its organisms.